Use of a hydrophilic coating wire reduces significantly the rate of central vein punctures and the incidence of pneumothorax in totally implantable access port (TIAP) surgery - Polychronidis, Georgios; Hennes, Roland; Engerer, Cosima; Knebel, Phillip; Schultze, Daniel; Bruckner, Thomas; Müller, Beat P.; Fischer, Lars (BMC surgery, 2017)
Insertion of a Totally Implantable Access Port (TIAP) can be performed either via Central Vein Puncture (CVP) or Brachiocephalic Vein Cut-down (venous section-VS). The primary success rate of TIAP implantation using VS rarely ever achieves 100%. The objective of this study was to describe a modified VS approach using a hydrophilic coated wire (TVS).